The Influence of Digital Marketing for Tourism Businesses in the Era of Global Economic Recovery during a Pandemic Study on the Three Tourist Destinations at the Kopeng Area (Merbabu View, Embun Merbabu and Merbabu Park) - Meida Rachmawati; Sudiyono Sudiyono (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic is one of the causes of the decreasing interest in visiting a tourist attractions. Hence, it is the cause of the decrease in economic numbers in the tourism sector, especially in the Kopeng area. The monthly decreasing number of tourists is one of the background issues on how to invite prospective tourists to visit tourist attractions in the Kopeng area after the era of the covid 19 pandemic. The need for proper marketing to reach all potential tourists encourage tourism sector managers in the Kopeng area to use social media facilities to re-market new tourism trends so that the economy recovers as before. The study involved 100 respondents, while the data was collected through questionnaires and then processed using SPSS data analysis techniques. The results of this study are: 1) There is a positive and significant relationship between digital marketing variables on economic recovery. 2) There is a positive and significant relationship between tourist visits and economic recovery variables.